Single centre, real‐world experience of perioperative rFIXFc use in adult patients with haemophilia B undergoing major and minor surgery. Issue 6 (6th October 2021) - O'Donovan, Mairead; Singleton, Evelyn; Roche, Sheila; McGowan, Mark; Benson, Julie; Bergin, Catherine; Bird, Rachel; Byrne, Mary; Duggan, Cleona; Gilmore, Ruth; Ryan, Kevin; Dougall, Alison; et al.
Abstract: Introduction: Recombinant factor IX fusion protein concentrate (rFIXFc) is increasingly used for prophylaxis in people with haemophilia B (PWHB), but experience in the perioperative setting is limited. Aims: To evaluate real‐world perioperative factor usage, bleeding and complications in PWHB (≥18 years) who received rFIXFc for surgical haemostasis and to describe the treatment regimens used. Methods: Single centre, retrospective review of all PWHB who underwent a major or minor surgical procedure between June 2017 and July 2020 and received rFIXFc perioperatively for maintenance of surgical haemostasis. Results: A total of 56 PWHB (45 male and 11 female), including people with mild (n = 32), moderate (n = 4) and severe (n = 20) haemophilia B, underwent 11 major and 131 minor procedures with rFIXFc for surgical haemostasis. Haemostasis was rated as excellent (9/11) or good (2/11) in all major procedures. Median total rFIXFc consumption for orthopaedic surgeries was 972 IU/kg (range 812–1031 IU/kg) and for other major (non‐orthopaedic) surgeries was 323 IU/kg (range 167–760 IU/kg). The median number of perioperative rFIXFc infusions was 19 (range 17–26) for orthopaedic surgery and 7 (range 5–17) for other major surgeries. The number of infusions in the postoperative period was determined by procedure and patient factors. Complications included bowel ileus and wound infection. Most minor procedures were managed with single infusion of rFIXFc, with no bleeding complications in 95% of minor procedures. There were no thromboembolic events or inhibitor formation. Conclusion: This unique data provides real‐world evidence that rFIXFc is safe and effective in achieving haemostasis in PWHB undergoing surgery.